Beyond here, beyond now, beyond human: reflecting on ghostly presences in field research. (April 2017) - Edwards, Amanda
The research encounter can be understood as an interaction between an individuated researcher positioned inside or outside a community or culture, a more fluid researcher testing and sometimes crossing the permeable boundaries of a shifting community, or a brief, fragile entanglement of dynamic trajectories. Within this last, relational approach, previous work identifies the agency of multiple past and present human social relationships in the co-construction of the research story, however, there has been limited reflection on (bio)physical, geographical, artefactual and other more-than-human entanglements. In this article, I use a creative, non-fiction approach to describe the processes, and challenges, involved in developing a dynamic, relational understanding of research encounters through an exploration of how (bio)physical, geographical, artefactual and other presences interact with ghostly geographies, histories and imaginaries in persons and places to influence the generation and analysis of research data.